2019
DOI: 10.1016/j.omtn.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Long Non-coding RNA ENST00000507296 Is a Prognostic Indicator in Patients with Dilated Cardiomyopathy

Abstract: Background: Long non-coding RNAs (lncRNAs) participate in the pathogenesis of cardiovascular diseases. However, whether circulating lncRNAs serve as dilated cardiomyopathy (DCM) biomarkers remains unclear. Methods: Totally, 266 controls and 818 patients were enrolled. First, microarray-based circulating lncRNA profiling was performed in 10 normal controls and 10 patients with DCM. Second, the top 20 differentially expressed lncRNAs were validated by real-time qPCR in 64 controls and 64 DCM patients. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 47 publications
(63 reference statements)
2
15
0
Order By: Relevance
“…DCM accounts for about one-third of heart failure patients. A recent study reported that lncRNAs ENST00000532365 and ENST00000507296 could serve as biomarkers for the diagnosis of DCM-related heart failure (36). In the present study, we found that XIST presented an AUC of 0.733, and IDI2-AS1 exhibited an AUC of 0.796.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…DCM accounts for about one-third of heart failure patients. A recent study reported that lncRNAs ENST00000532365 and ENST00000507296 could serve as biomarkers for the diagnosis of DCM-related heart failure (36). In the present study, we found that XIST presented an AUC of 0.733, and IDI2-AS1 exhibited an AUC of 0.796.…”
Section: Discussionsupporting
confidence: 65%
“…DCM is usually diagnosed at ages between 30 and 40 years of age. However, owing to the vague symptoms and delay in diagnosis, the outcome for DCM is poor (36). DCM accounts for about one-third of heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Arrows point to the transcriptional directions of MYH6 and MYH7 genes. (D) Heatmap illustrates the rank of the average expression across all studied samples for circRNAs produced from MYH6 and MYH7 genes in this study, and in human, mouse and rat hearts as identi ed by Tan et al [12] and Werfel et al [11]. The…”
Section: Consent For Publicationmentioning
confidence: 74%
“…Analysis of circRNAs from MYH6 and MYH7 gene. (A) Schematic diagram showing a number of rt-circRNAs originate from MYH6 and MYH7 genes in human heart identi ed in this study, study of Tan et al [12] and Werfel et al [11], and in (B) mouse heart identi ed in this study and study of Werfel et al [11], as well as in (C) rat heart revealed in the study of Werfel et al [11]. Arrows point to the transcriptional directions of MYH6 and MYH7 genes.…”
Section: Consent For Publicationmentioning
confidence: 77%
“…Therefore, it is likely that other unknown genetic factors await discovery. The aberrant expression of different types of RNA transcripts, including those transcribed from protein coding genes [ 7 9 ], long non-coding genes [ 10 , 11 ] and miRNAs [ 12 14 ], have been observed in DCM.…”
Section: Introductionmentioning
confidence: 99%